Chemical Aspects of Drug Delivery - Stephenson, R. A. (Springer, 1996)
Annotation The April 1996 proceedings address the challenges of developing drugs with delivery systems that target the correct organ and achieve the necessary level of drug in the body. New materials and systems for drug delivery targeting are reviewed in the 15 presentations, including aspects of bioadhesive polymers, novel nonionic surfactant vesicles, hydrogels based on poly(ethylene glycols), monofunctional poly(ethylene glycol), and aqueous shellac solutions. Annotation c. by Book News, Inc., Portland, Or.
Keywords: Drug delivery systems -- Congresses.; elektronické knihy; electronic books